Software Projects and Software Project Risks - Kuukkanen, Sari (2007)
Bachelor s thesis in Information Systems / Sari Kuukkanen Jyväskylä: University of Jyväskylä, 2007, 26 pp. Bachelor s thesis Software projects have proven to be complex with many interactions and dependencies. Many software projects overrun schedules, exceed their budgets, and produce unsatisfactory outcome. Third of all software projects end in failure and are cancelled outright. When unpredictable events arise in a project, they can become risks, which are a threat to the completion of the project. Risk management is a collection of methods that reduce the negative effects of risks. By identifying risks at early stages of the product lifecycle risks can be dealt with accordingly, which secures the successful completion of projects. This thesis conducted as a literature review. It introduces software projects and identifying risks in them. It offers a compact theory review for understanding why software projects fail and how risks in software projects are identified and assessed with risk management tools. The relevant concepts are introduced: project, project management, risk, risk exposure, risk management, and risk management framework. The goal of this study is to investigate special characteristics of software projects and introduce a risk categorisation framework for identifying risks that threaten the success of projects.